Great expectations - Dickens, Charles (Oxford University Press, 2007)
This book is about the progress of Pip from childhood to adulthood and it shows the dangers of being driven by a desire for wealth and social status. As Pip moves from the Kent marshes to busy, commercial London, encountering many extraordinary characters--from Magwitch, the escaped convict, to Miss Havisham, a woman locked up with her past--he is confronted with the challenge of establishing a sense of his own identity and values contrary to the plans others have for him.